Trade, Trust And The Territoriality Of The Law - Dieter Schmidtchen; Alexander R. Neunzig (Universität des Saarlandes, Center for the Study of Law and Economics (CSLE), 1997)
In this paper we analyze whether trust can overcome the contractual hazards caused by the territoriality of law, how effective trust is and what the impact is on the sequential structure of trade. The paper contributes to the New Institutional Economics of International Transactions (NIEIT). – – In diesem Paper wird untersucht, inwiefern Vertrauen die durch die Territorialität des Rechts verursachten vertraglichen Risiken mildern kann, wie effektiv Vertrauen ist, und welcherart seine Auswirkungen auf die sequentielle Struktur des Handels ist. Das Paper stellt einen Beitrag zur Neuen Institutionenökonomik internationaler Transaktionen dar (NIIT) dar.
Keywords: K12; C72; 330; international contract enforcment; trust game; bounded rationality; Vertragsrecht; Nationalstaat; Internationales Handelsrecht; Außenwirtschaft; Vertrauen; Spieltheorie; Theorie